2013
DOI: 10.1002/zaac.201300060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cis‐ and Oxaliplatin‐induced Destabilization of 15‐mer DNA‐ and RNA Duplexes by Binding to Centrally Located GG‐ and GNG Sequences

Abstract: Abstract. Thermodynamic parameters are presented here illustrating the effects caused by the two anticancer active metal complexes cisplatin and oxaliplatin after introduction into four closely related RNA and DNA duplexes. The duplexes used are blunt end, fully complementary 15-mer duplexes with a centrally located either GG-or GNG (here: N = T or U) binding site. For all duplexes, a common trend of reduced melting temperature was observed after platination. Analysis of the thermodynamic parameters for the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…80,[82][83][84] Negative values of DT m indicate covalent binding. [85][86][87] In the case of 1, the difference in melting temperatures DT m (DT m ¼ T m of free DNA -T m of DNA-1) is À4.5 C (Fig. 6), corroborating uorescence quenching studies which show that 1 does not have a signicant propensity to minor groove and does not intercalate.…”
Section: Fluorescence Quenching Studiessupporting
confidence: 73%
“…80,[82][83][84] Negative values of DT m indicate covalent binding. [85][86][87] In the case of 1, the difference in melting temperatures DT m (DT m ¼ T m of free DNA -T m of DNA-1) is À4.5 C (Fig. 6), corroborating uorescence quenching studies which show that 1 does not have a signicant propensity to minor groove and does not intercalate.…”
Section: Fluorescence Quenching Studiessupporting
confidence: 73%
“…Both these duplexes have recently been characterized with respect to thermodynamic properties and the effects of cisplatin binding. 32 At the salt concentrations investigated, these RNAs have similar melting temperatures, see Table 1, ca. 47 and 60 °C at C Na+ = 29 and 129 mM, respectively.…”
mentioning
confidence: 87%
“…10 °C for RNA-1 and 18 °C for RNA-2. 32 Based on these observations, we have speculated that when subjected to cisplatin at a temperature just below the melting point, the expected metal-induced melting of these duplexes could be used to directly monitor the rate of platinum binding. An example of the spectral changes on addition of 1a to RNA-1 is shown in Fig.…”
mentioning
confidence: 99%
“…4), and the corresponding DNA duplexes. They showed that both the two platinum complexes strongly destabilize the duplexes, resulting in melting temperature reduction, with a much larger destabilization observed for the GXG containing duplexes than for the GG containing ones, especially for the RNA species [94]. Following this study, they established a quick methodology to investigate the platination kinetics of different RNA duplexes, that relies on monitoring platinum-induced duplex destabilization via UV-Vis spectroscopy in the presence of the mono-aquated form of cisplatin.…”
Section: Kinetics Of Rna-platinum Binding Studied Via Uv-vis: How Difmentioning
confidence: 97%